La relación entre Pedro I y el Concejo de León - Rodríguez López, María del Carmen (Estudios humanísticos. Geografía, historia y arte, 1995)
A study on Pedro 1 government, and his favourable politics towards the Leon's town council, during the first ten years under the reign of Pedro 1 "el cruel".